Sustainable clay soil stabilization using constructions waste: Mechanical behavior, engineering parameters and microstructural analysis - Alireza Nezhadesmaeel Tavala; Abdollah Tabaroei (Results in Engineering, 2025)
Sustainably improving clay soils is a key challenge in geotechnical engineering, with increasing focus on reducing the environmental impacts of traditional stabilization methods. This study proposes an eco-friendly alternative by utilizing granite-cutting waste (G-CW) and cemented slurry waste (CSW), offering a dual advantage of waste valorization and enhanced soil properties. Unlike cement, which relies on high-energy production processes, or gypsum, which has limited long-term durability in wet conditions, G-CW and CSW provide a sustainable solution with lower environmental costs. The investigation, conducted on clayey soils along the Torbat-e-Heydarieh–Mashhad Road in Iran, the experimental program involved incorporating of about 12 kg of G-CW and CSW at 8 %, 16 %, and 32 % by weight of dry soil, with a 1:1 proportion of the two additives. The process included Atterberg limits, compaction and unconfined compressive strength (UCS) tests, alongside advanced microstructural analyses (XRD, XRF, FTIR and SEM) to understand the underlying stabilization mechanisms. The inclusion of G-CW and CSW significantly reduced the soil’s plasticity index >85 %, while UCS values exhibited a remarkable increase from 64 kPa to approximately 450 kPa. This enhancement translated into notable improvements in engineering parameters, such as the secant modulus (Es) and resilient modulus (MR) indicating the suitability of this method for field applications. As a result of using recycled construction waste, this study not only presents an environmentally sustainable approach to soil stabilization but also highlights the feasibility of incorporating circular economy principles into geotechnical engineering practices.